Effectiveness of project-based MKWK learning model - Sahru Romadloni; Elok Rosyidah (Universitas Negeri Yogyakarta, 2026)
The development of a project-based MKWK learning model is based on the need to develop implementation guidelines, learning tools, and institutional integration of MKWK implementation. The learning process is also often carried out in the classroom, so it is not in line with the MBKM curriculum. The purpose of this study is to develop a project-based MKWK learning model to increase student lecture participation. The research method used is Research and Development (R&D) research with the A.D.D.I.E. development model consisting of five stages; Analysis, Design, Development, Implementation, Evaluation, but simplified as needed due to time constraints and other factors into three steps; (1) Analysis, (2) Development, and (3) Evaluation. Based on the results of statistical tests, there is a significant difference between the experimental target and the control target. Statistical tests were carried out using the SPSS program. The results show that the post-test gain for the experimental target was 84, and the average post-test for the control target was 76.3. Meanwhile, the T test obtained a value of 6.621 with a significance level of 0.000 lower than 0.025 (0.000 < 0.025), which indicates that Ho is rejected, the results obtained are the difference between the experimental target and the control target. In conclusion, the project-based MKWK learning model at the University of 17 August 1945 Banyuwangi that was developed is effective in increasing lecture participation